Elucidating hepatic lipidosis in stray cats through serum biochemistry, liver histopathology and liver RNA expression of PPAR-δ and PPAR-γ - F. Salleh,; Goh, Y.M.; Lau, S.F.; P.A.M.A. Rani,; R. Radzi,; M. Mazlan,; A.R. Alashraf,; Goh, S.H.; S.A. Rahman,; T.B.M. Mohidin,; M.N. Akmal,; A.N. Ilias,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Early detection of feline hepatic lipidosis (FHL) with appropriate treatment can increase prognosis significantly. This study looks into the serum biochemistry and lipid composition of serum and liver samples in a group of stray cats (N=18) collected from pounds in Klang Valley, Malaysia. Alanine aminotransferase (ALT) in blood serum was used to detect for liver damage possibly due to FHL, confirmed through light microscopy, serum biochemistry (triglyceride, cholesterol, creatinine, and urea), liver triglyceride and cholesterol concentrations, and liver RNA expression of lipid droplet regulators peroxisome proliferator-activated receptors (PPARs). Differing severity of FHL in samples were divided and grouped using an adapted scoring method observing fatty change of liver (FCL) with trends between FCL groups investigated. Elevated serum ALT reflective of increasing FCL severity was observed with elevated concentrations of liver TAG and cholesterol levels. Serum TAG and cholesterol decreased with heightened FCL pointing to fatty acid oxidation and lipid restoration in the liver, supported by PPAR-γ expression which also propose macrophage activation for liver recovery alongside PPAR-δ for lipogenesis and inflammatory reactions. Elevated serum creatinine and urea levels with increasing FCL severity propose overall intact hepatic function in the stray cat samples.